Pseudomonas aeruginosa Stimulates Inflammation and Enhances Kaposi’s Sarcoma Herpesvirus-Induced Cell Proliferation and Cellular Transformation through both Lipopolysaccharide and Flagellin - Ashley Markazi (American Society for Microbiology, 2020)
ABSTRACT Inflammation triggered by innate immunity promotes carcinogenesis in cancer. Kaposi’s sarcoma (KS), a hyperproliferative and inflammatory tumor caused by Kaposi’s sarcoma-associated herpesvirus (KSHV) infection, is the most common cancer in AIDS patients. KSHV infection sensitizes cells to pathogen-associated molecular patterns (PAMPs). We examined the role of Pseudomonas aeruginosa, an opportunistic bacterium that can affect AIDS patients, in inflammation and cell proliferation of KSHV-transformed cells. P. aeruginosa stimulation increased cell proliferation and efficiency of colony formation in soft agar of KSHV-transformed rat primary mesenchymal precursor (KMM) cells but had no significant effect on the untransformed (MM) cells. P. aeruginosa stimulation also increased cell proliferation of KSHV-infected human B cells, BJAB, but not the uninfected cells. Mechanistically, P. aeruginosa stimulation resulted in increased inflammatory cytokines and activation of p38, ERK1/2, and JNK mitogen-activated protein kinase (MAPK) pathways in KMM cells while having no obvious effect on MM cells. P. aeruginosa induction of inflammation and MAPKs was observed with and without inhibition of the Toll-like receptor 4 (TLR4) pathway, while a flagellin-deleted mutant of P. aeruginosa required a functional TLR4 pathway to induce inflammation and MAPKs. Furthermore, treatment with either lipopolysaccharide (LPS) or flagellin alone was sufficient to induce inflammatory cytokines, activate MAPKs, and increase cell proliferation and efficiency of colony formation in soft agar of KMM cells. These results demonstrate that both LPS and flagellin are PAMPs that contribute to P. aeruginosa induction of inflammation in KSHV-transformed cells. Because AIDS-KS patients are susceptible to P. aeruginosa infection, our work highlights the preventive and therapeutic potential of targeting P. aeruginosa infection in these patients. IMPORTANCE Kaposi’s sarcoma (KS), caused by infection with Kaposi’s sarcoma-associated herpesvirus (KSHV), is one of the most common cancers in AIDS patients. KS is a highly inflammatory tumor, but how KSHV infection induces inflammation remains unclear. We have previously shown that KSHV infection upregulates Toll-like receptor 4 (TLR4), sensitizing cells to lipopolysaccharide (LPS) and Escherichia coli. In the current study, we examined the role of Pseudomonas aeruginosa, an opportunistic bacterium that can affect AIDS patients, in inflammation and cell proliferation of KSHV-transformed cells. P. aeruginosa stimulation increased cell proliferation, inflammatory cytokines, and activation of growth and survival pathways in KSHV-transformed cells through two pathogen-associated molecular patterns, LPS and flagellin. Because AIDS-KS patients are susceptible to P. aeruginosa infection, our work highlights the preventive and therapeutic potential of targeting P. aeruginosa infection in these patients.